Judge's Dilemma in Marriage Dispensation in the Religious Court - Lahilote, Hasyim Sofyan; Miftah, A.A.; Yuliatin, Yuliatin; Hidayati, Rahmi (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2022)
Judges experience various dilemmas when adjudicating marriage dispensation cases in Religious Courts. In particular, there are difficulties associated with applying the principles laid out in the provisions of Article 2 PERMA no. 5 of 2019, which guide such decisions. This study analyzes how judges consider various legal theories when making decisions regarding marriage dispensations using the normative judicial method. The results showed that the judges of Religious Courts primarily rely on the maslahah theory when making decisions on marriage dispensation cases, in spite of the existence of PERMA no. 5 of 2019 as a potential reference for maximizing aspects of justice and legal certainty.